Revenge of the Aztecs - Pfeffer, Susan Beth, 1948- (Lincolnwood, Ill. : Jamestown Publishers, 2000)
In 1923, fourteen-year-old Alicia Martinez is cast in an important silent movie role by her best friend's father, but near-disasters on the Hollywood set seem to be directed at her, and almost anyone could be responsible
Keywords: Silent films -- Fiction; Actors and actresses -- Fiction; Motion pictures -- Production and direction -- Fiction; Friendship -- Fiction; Orphans -- Fiction; Mystery and detective stories; Hollywood (Los Angeles, Calif.) -- Fiction